1999
DOI: 10.1097/00001756-199908020-00031
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid promotes rod photoreceptor differentiation in rat retina in vivo

Abstract: Previous studies have indicated that retinoic acid (RA) promotes rod photoreceptor differentiation in dissociated cultures of rat retina and in zebrafish embryos. To determine whether RA will have the same affect in the mammalian retina in vivo, pregnant rats were given single i.p. injections of RA on the 18th and 20th days of gestation, and the retinas of the pups were analyzed for rods. HPLC showed that i.p. injections of RA substantially increased levels of retinal RA in the embryos. Embryonic exposure to R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
145
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(157 citation statements)
references
References 6 publications
8
145
0
4
Order By: Relevance
“…We consider three areas where RA plays a role in differentiation: in photoreceptors, hippocampus, and cortical neurons. RA can cause dissociated, neonatal rat retinas in culture to differentiate into photoreceptor cells expressing rhodopsin and/or recoverin [71]. Human, mouse, and monkey embryonic stem cells can also be differentiated into rod photoreceptors, albeit more laboriously, due to the requirement of an intermediate step of Notch inactivation, followed by a cocktail containing RA, Shh, FGFs, and taurine [72].…”
Section: Primary Neurogenesis In Anamniotes Versus Amniotesmentioning
confidence: 99%
“…We consider three areas where RA plays a role in differentiation: in photoreceptors, hippocampus, and cortical neurons. RA can cause dissociated, neonatal rat retinas in culture to differentiate into photoreceptor cells expressing rhodopsin and/or recoverin [71]. Human, mouse, and monkey embryonic stem cells can also be differentiated into rod photoreceptors, albeit more laboriously, due to the requirement of an intermediate step of Notch inactivation, followed by a cocktail containing RA, Shh, FGFs, and taurine [72].…”
Section: Primary Neurogenesis In Anamniotes Versus Amniotesmentioning
confidence: 99%
“…In particular, it was shown that factors present in the postnatal rat or mouse retina promoted the development of rhodopsin-expressing cells in the cultures. These initial findings were followed by studies that aimed to define the 'rod-inducing' molecule in postnatal cultures, and eventually both taurine and retinoic acid were found to promote rhodopsin expression in cultures of retinal cells (Altshuler et al, 1993;Kelley et al, 1994). Other soluble factors, such as activin and Shh, also promote rhodopsin expression in some in vitro assays (Levine et al, 1997(Levine et al, , 2000Davis et al, 2000).…”
Section: Signaling Molecules Involved In Photoreceptor Fate Specificamentioning
confidence: 99%
“…In addition to a role for RA in regulating eye morphogenesis, several in vitro experiments in nonteleost vertebrate model systems have revealed that RA promotes photoreceptor differentiation, photoreceptor survival, and the generation of photoreceptors at the expense of other retinal cell types (Kelley et al, 1994;Soderpalm et al, 2000;Stenkamp et al, 1993). However, in vivo experiments in zebrafish have not supported a role for RA in regulating photoreceptor cell fate (Hyatt et al, 1996a;Prabhudesai et al, 2005).…”
Section: Extrinsic Factorsmentioning
confidence: 99%